Mitigation of Land Movement using Self Potential Method in Ling-Anjung Region Sumedang Regency - Budy Santoso; Setianto Setianto; M U Hasanah; B Wijatmoko; E Supriyana; H Mohammad (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
Land movement occurs due to reduced soil strength which is affected by water pressure. The Self Potential (SP) method is a geoelectric method that can detect well the flow of groundwater. The Self Potential method can also be used to detect the presence of debris flow in the form of weathered soil, tuff sand, cobble gravel and other rock fragments that have mixed with water. Based on the results of the SP measurement, debris flow has a medium SP with a value (3 - 12) mV, rock that has shifted (sandstone associated with andesite fragment) has a SP value < 2mV, while water seepage and water flow has an SP value (13 - 36) mV.